Bond ionicity, lattice energy and structural evolution of Ta substituted 0.15ZnO-0.15Nb2O5-0.55TiO2 dielectric ceramics - Chen, Yawei; Zhang, Shuren; Yang, Hongyu; Yang, Hongcheng; Yuan, Ying; Li, Enzhu (Ceramics international, 2019)
In the present study, influences of Ta5+ substitution on Nb site on crystal structural evolution, Raman spectra and microwave dielectric properties of Zn0.15Nb0.3-xTaxTi0.55O2 (0 ≤ x ≤ 0.3) ceramics were investigated. Bond ionicity, lattice energy and octahedral distortion of Zn0.15Nb0.3-xTaxTi0.55O2 structure calculated based on chemical bond theory and Rietveld refinement analysis were used together to understand correlation between crystal structure and microwave dielectric properties. The results showed that rutile Zn0.15Nb0.3-xTaxTi0.55O2 solid solutions could be synthesized in whole composition range of x = 0–0.3. With increase of x value, cell volume and bond length are reduced, which is confirmed by blue shift of Raman vibrational peaks. Dielectric constant (εr) is closely related to average NbO bond ionicity. Quality factor (Q × f) values and temperature coefficient values of resonant frequency (τf) are mainly affected by lattice energy and octahedral distortion respectively. In Zn0.15Nb0.3-xTaxTi0.55O2 ceramics, proper substitution of Ta5+ ion efficiently improves Q × f values and reduces the τf values. Optimal microwave dielectric properties of εr = 75.87, Q × f = 22050 GHz and τf = 234.6 ppm/°C were obtained for Zn0.15Nb0.3-xTaxTi0.55O2 solid solutions at x = 0.2 when sintered at 1100 °C.